Nanowire Memristors: Recent Developments and Perspectives for Memristive Devices Based on Metal Oxide Nanowires (Adv. Electron. Mater. 9/2019). (9th September 2019) - Milano, Gianluca; Porro, Samuele; Valov, Ilia; Ricciardi, Carlo
Abstract : In article number1800909, Ilia Valov, Carlo Ricciard, and co‐workers review state‐of‐the‐art memristive and neuromorphic devices based on nanowires. Resistive switching performances and synaptic functionalities of single isolated nanowires, nanowire arrays and random networks are analyzed, with a focus on the physical and chemical mechanisms underlaying resistive switching events. Challenges and future perspectives on nanowire based‐memristors are discussed.